2019
DOI: 10.1080/1331677x.2019.1588766
|View full text |Cite
|
Sign up to set email alerts
|

Cultural, cognitive and personality traits in risk-taking behaviour: evidence from Poland and the United States of America

Abstract: The study analyses the susceptibility to risk-taking behaviour in relation to cultural, cognitive and personality traits. For the requirements of the research, undergraduate students with the same major but from two different cultural regions (Poland and the USA) were examined. In order to better understand them, the ten-item personality inventory (TIPI) methoda 10-item measure of the Big-Five personality dimensionswas used. A domain-specific risk-taking (DOSPERT) scale was used to assess risk-taking, while co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
3
15
1
5
Order By: Relevance
“…Cecchini et al (2019) also highlighted the importance of openness to experience to better value information to achieve higher outcomes. Czerwonka (2019) showed, as many others have before, that Extraversion (positively) and Conscientiousness (negatively) were related to risk-taking; and that men were greater risk takers than women. Durand, Fung, and Limkriangkrai (2019) were interested in myopic loss aversion.…”
Section: Personality and Financial Decision Makingsupporting
confidence: 73%
“…Cecchini et al (2019) also highlighted the importance of openness to experience to better value information to achieve higher outcomes. Czerwonka (2019) showed, as many others have before, that Extraversion (positively) and Conscientiousness (negatively) were related to risk-taking; and that men were greater risk takers than women. Durand, Fung, and Limkriangkrai (2019) were interested in myopic loss aversion.…”
Section: Personality and Financial Decision Makingsupporting
confidence: 73%
“…According to their findings, people’s personality traits influence their investment-related risk preferences, such that if investors exhibit outgoing, prudential personality traits, they accept more investment risk. Czerwonka (2019), based on her research conducted in two different cultural regions, namely Poland and the USA, concludes that high extraversion and low conscientiousness are predictors of overall risk-taking behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have shown that the CRT predicts susceptibility to decision-making biases and heuristics (Duttle and Inukai 2015;Oechssler et al, 2009;Toplak et al, 2011;, risk-taking behavior (Frederick, 2005;Czerwonka, 2019) and that it is not just a mathematical test but measures something above and beyond general skills, namely cognitive reflection (Campitelli and Gerrans, 2014).…”
Section: Cognitive Reflection Testmentioning
confidence: 99%